2013
DOI: 10.1177/0165025413509046
|View full text |Cite
|
Sign up to set email alerts
|

Does visual attention span relate to eye movements during reading and copying?

Abstract: This research investigated whether text reading and copying involve visual attention-processing skills. Children in grades 3 and 5 read and copied the same text. We measured eye movements while reading and the number of gaze lifts (GL) during copying. The children were also administered letter report tasks that constitute an estimation of the number of letters that are processed simultaneously. The tasks were designed to assess visual attention span abilities (VA). The results for both grades revealed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…These results indicate that the significance of visual attention span in reading Chinese, particularly in traditional Chinese, is found not only in children but also in adults. Furthermore, correlations of similar magnitude have been found between the global report and reading fluency among children, 0.38 < rs < 0.59 (Bosse et al, 2014), and adults, r = 0.46 in French (Awadh et al, 2016). The similar pattern across children and adults among Chinese and French suggests that the relationship between visual attention span reading may be universal and is not limited to a particular orthography.…”
Section: Prediction Of Chinese Reading Fluencysupporting
confidence: 55%
See 1 more Smart Citation
“…These results indicate that the significance of visual attention span in reading Chinese, particularly in traditional Chinese, is found not only in children but also in adults. Furthermore, correlations of similar magnitude have been found between the global report and reading fluency among children, 0.38 < rs < 0.59 (Bosse et al, 2014), and adults, r = 0.46 in French (Awadh et al, 2016). The similar pattern across children and adults among Chinese and French suggests that the relationship between visual attention span reading may be universal and is not limited to a particular orthography.…”
Section: Prediction Of Chinese Reading Fluencysupporting
confidence: 55%
“…Numerous studies have shown that visual attention span is significantly correlated with reading ability in alphabetic languages among children, such as in French, English, Portuguese, Spanish, and Dutch (Bosse et al, 2014;Germano et al, 2014;van den Boer et al, 2015;Chen et al, 2016;Antzaka et al, 2018), and adults, such as in French and Arabic (Awadh et al, 2016;Antzaka et al, 2017). After age, IQ, and phonological awareness are controlled for, visual attention span serves as a unique predictor of the French and English reading accuracy (Bosse et al, 2007;Bosse and Valdois, 2009), French reading fluency (Bosse and Valdois, 2009), and Dutch reading fluency (van den Boer et al, 2013(van den Boer et al, , 2015 of junior-grade children.…”
Section: Introductionmentioning
confidence: 99%
“…to attend to a higher number of letters during reading. Therefore, children learning to read in opaque orthographies may preferentially try to distribute their visual attention span resources widely, and focus on several visual elements at once (see Bosse, Kandel, Prado & Valdois, ) to access the accurate phoneme(s). This visual strategy may further boost the acquisition of word‐specific orthographic knowledge in opaque languages (Bosse et al ., ; Bosse, Chaves, Largy & Valdois, ).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that VAS essentially affects reading speed suggests that a large VAS favours the fast whole-word procedure of reading (Lobier, Dubois, & Valdois, 2013) and permits more letters at each fixation to be processed. It has consistently been observed that in children, a larger VAS is associated with fewer rightward fixations during text reading (Bosse, Kandel, Prado, & Valdois, 2014;Prado, Dubois, & Valdois, 2007). On the whole, a significant number of studies have provided evidence that VAS is an important predictor of child reading performance in both transparent and opaque alphabetic languages.…”
Section: Visual Attention Spanmentioning
confidence: 99%
“…More specifically, the French-Basque bilinguals showed more efficient visual processing strategies than Spanish-Basque bilinguals when performing VAS tasks (Lallier et al, 2016). It has been well established that skilled readers of opaque languages process words as a whole, and children learning to read in opaque orthographies may preferentially try to distribute their VAS resources widely and focus on several visual elements at once (see Bosse et al, 2014). In adult skilled readers, VAS was more reduced in Arabic readers compared to French or Spanish readers (Awadh et al, 2016).…”
Section: Visual Attention Spanmentioning
confidence: 99%